Exploring the Feasibility of HRMN-99 Apple Variety Cultivation in Sub-Tropical Regions of Nepal: Bridging Tradition and Innovation - Chhatkuli, Shyam Bahadur (International Research Journal of MMC, 2023)
Traditionally, Nepal's apple production flourished in higher altitudes, but the introduction of HRMN-99 brings the possibility of extending cultivation to subtropical locations. This study investigates the adaptability and performance of the HRMN-99 variety in sub-tropical area of Nepal, investigating into its growth, yield, and responses to local conditions. Through careful field experiments and data collection, this research sheds light on the variety's possibility in diverse climates. Literature reviews and citations from various sources underscore the significance of apple cultivation, highlighting the economic, health, and cultural dimensions. The findings reveal the potential for HRMN-99 to bridge the gap between tradition and innovation in Nepal's agricultural landscape. This research not only presents scientific insights but also opens possibilities for sustainable agricultural practices and economic growth of apple in sub-tropical region.